2005
DOI: 10.4067/s0717-77122005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Parásitos en aguas del arroyo Naposta, aguas de recreación y de consumo en la ciudad de Bahia Blanca (Provincia de Buenos Aires, Argentina)

Abstract: The aim of the present study was to detect the presence of sanitarily important parasites in the water from Arroyo Napostá as well as in the water used for recreational purposes (public swimmingpools)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
1
0
6
Order By: Relevance
“…Previous research in people from Villa Nocito reported the presence of antibodies against Toxocara spp. in 18% of the studied subjects, 18 whereas another work found that 83% of water samples from a natural stream that crosses the city were contaminated with Toxocara spp. eggs.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research in people from Villa Nocito reported the presence of antibodies against Toxocara spp. in 18% of the studied subjects, 18 whereas another work found that 83% of water samples from a natural stream that crosses the city were contaminated with Toxocara spp. eggs.…”
Section: Discussionmentioning
confidence: 98%
“…Cryptosporidium se eliminan al ambiente en gran número con las heces de los hospederos infectados y pueden contaminar fuentes de agua cruda (sin tratamiento) y suministros de agua de bebida (12,13,14,15,16,17). Además del hombre, existe un amplio rango de especies animales que pueden liberar en el ambiente estas formas infectantes, aumentado así su potencialidad de transmisión hídrica (11).…”
Section: Los Quistes De Giardia Y Los Ooquistes Deunclassified
“…Los autores indicaron que la giardiasis no siguió el patrón clásico (verano-otoño) observado en otros estudios y que podría deberse a eventos climáticos extremos como inundaciones en la región estudiada (Odoi et al, 2003;Mohamed et al, 2014). En Argentina, los quistes parasitarios fueron hallados en aguas de consumo y ambientales (Basualdo et al, 2000;Costamagna et al, 2005;Molina 2009;Molina et al, 2011).…”
Section: Discussionunclassified